Tax System and Equity Investment in a Growing Economy - C. O. Omodero (Финансы: теория и практика)
The purpose of the study is to identify the impact of the tax system on investment in equity capital by analyzing the six types of taxes that affect the activities of firms. The data for the independent variables (tax classes in Nigeria) are obtained from the Federal Internal Revenue Service, while the data for the dependent variable (equity investment) are obtained from the Statistical  Bulletin  of  the  Central  Bank of  Nigeria. The  necessary statistical  methodologies are used to examine the impact of various tax classes on equity investment from 2011 to 2020. According to the research, capital gains tax and  gas  income  tax have  little  effect  on  equity investment. The  petroleum  profit  tax and corporate income tax have a considerable detrimental impact on equity investment. On  the  plus  side, value added tax and education tax have a significant favorable impact on equity investment. These results are one-of-akind and precisely depict the genuine nature of the country’s tax system and its impact on investment. As a result, the research proposes a tax shift to lessen the tax burden on enterprises in order to stimulate equity investment, which will increase firms’ capital base for the purpose of business expansion and growth of the nation’s economic structure.